One Italian Summer : A Novel - Serle, Rebecca (New York, NY : Atria Books, an imprint of Simon & Schuster, Inc., 2022)
"When Katys mother dies, she is left reeling. Carol wasnt just Katys mom, but her best friend and first phone call. To make matters worse, the mother-daughter trip of a lifetime looms: two weeks in Positano. Katy has been waiting years for Carol to take her, and now she is faced with embarking on the adventure alone. But as soon as she steps foot on the beautiful Amalfi Coast, Katy begins to feel her mothers spirit. And then Carol appears for real--in the flesh, healthy and sun-tanned ... and thirty years old. Katy doesnt understand what is happening, or how. But over the course of her time in Italy, Katy gets to know Carol in this new form, and soon she must reconcile the mother who knew everything with the young woman who does not yet have a clue."--
Keywords: Mothers -- Death; Fiction; Mothers and daughters -- Fiction; Female friendship -- Fiction; Positano (Italy) -- Fiction; Domestic fiction; Romance fiction